(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The artist Leonora Carrington has awakened increasing interest in feminist and art history studies, among other reasons, for the feminist poetics developed throughout her long career. This feminist poetics accompanies immersion into the unconscious, alchemic transformation and transmutation shrouded by an oneiric narrative that displaces the concept of dream solely as the expression of repressed desire. Thus, this work purports to debate, from a dialogue with theories that examine the dream as an opening to the knowledge of the self, how the oeuvre of Carrington can open breaches in the schisms of a binary patriarchic culture. To that end, two paintings by the artist that illustrate and complement the analysis will be further analyzed. Keywords: Leonora Carrington, dreams, surrealism, feminisms, borderspace.